Coping Strategies: an alternative to face situations that produce burnout - Marsollier, Roxana Graciela; Aparicio, Miriam Teresita (Instituto de Investigaciones Psicológicas, 2010)
The objective of this paper is to study Coping Strategies as explanatory variables of Job Burnout, in employees (University graduates vs. non-university graduates) working at government offices in Mendoza Argentina. In order to develop a more comprehensive approach to this issue, the methodology used includes quantitative techniques and qualitative techniques. The research entailed a comparative study. The results obtained from the quantitative data, show significant differences between “university” graduates – who use strategies that seem to be closer to action and problem solving; and “non-university” graduates – who use strategies linked to emotion. From an applied point of view, it is expected that the results may generate Ongoing Training Programs focusing on burnout and stress related to the development of positive Coping Strategies.